The complete World Development Report 1978-2009 (World Bank, 2009)
This publication brings together the full texts of all 31 yearly development reports in a digital archive. It contains browsing features of all reports by title, year, and topic, an up-to-date database derived from World Development Indicators 2008, with time series data for 208 countries and 18 country groups, and a timeline of key World Bank and international events since 1945.--Publisher's description.